2014
DOI: 10.1063/1.4865497
|View full text |Cite
|
Sign up to set email alerts
|

Type-I superconductor pick-up coil in superconducting quantum interference device-based ultra-low field nuclear magnetic resonance

Abstract: Articles you may be interested inHigh-sensitivity cooled coil system for nuclear magnetic resonance in kHz range Rev. Sci. Instrum. 85, 114708 (2014); 10.1063/1.4901964 Nano-superconducting quantum interference devices with suspended junctions Appl. Phys. Lett.A nuclear magnetic resonance spectrometer for operation around 1 MHz with a sub-10 -mK noise temperature, based on a two-stage dc superconducting quantum interference device sensor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Both of these type-II superconductors trap magnetic flux during the pre-polarization time and generate flux jumps during the subsequent measurement time. This significantly increases the low-frequency noise with a typical 1/f-shaped spectrum [4,5]. We have observed significant 1/f noise below 6 kHz after niobium gradiometers were exposed to a 0.1 T field [6].…”
Section: Introductionmentioning
confidence: 84%
“…Both of these type-II superconductors trap magnetic flux during the pre-polarization time and generate flux jumps during the subsequent measurement time. This significantly increases the low-frequency noise with a typical 1/f-shaped spectrum [4,5]. We have observed significant 1/f noise below 6 kHz after niobium gradiometers were exposed to a 0.1 T field [6].…”
Section: Introductionmentioning
confidence: 84%
“…The SNR at higher fields could also be degraded because the critical field (H c1 ) of the PbSn solder (a type-II superconductor) coating used in our gradiometer is relatively low (80-200 mT). 14 In their recent work, Hwang et al 16 observed that the gradiometers made of type-II superconducting materials showed worse performance when operated above H c1 .…”
Section: B Imagingmentioning
confidence: 99%
“…The NMR signal is, thus, proportional to B p , which is electrically switched on and off. A stronger B p is, of course, advantageous for obtaining a stronger signal; however, it also creates unwanted side effects, such as the induction of eddy currents on the walls of a magnetically shielded room (MSR) [15][16][17] and flux trapping in superconducting pickup coils [24]. Both effects generate a temporally varying field, which broadens the NMR linewidth and distorts the MR image.…”
Section: Introductionmentioning
confidence: 99%